THE ELEMENTS THAT INFLUENCE THE PROFESSIONAL CONDUCT OF TEACHERS INVOLVED IN EARLY EDUCATION - Makrogiannaki, Aikaterini; Urea, Ionela Roxana I. (International Journal of Research -GRANTHAALAYAH, 2019)
Teachers that work with little children provide the first educational services and constantly have to pay attention to accomplish the educational goals that are suitable for these children. Therefore, they develop, according with their professional experience, a specific conduct which is reflected in all their actions. Our research had the aim to identify the elements that have impact upon professional conduct of teachers involved in early education and are relevant for quality of the early education The paper tries to reveal the elements the influence the conduct of teachers that are involved in early education of the children. In our research we used the “Questionnaire for assessing teachers professional conduct” b) the “Questionnaire for assessing conditions of teachers quality services provided”, non-directive interviews; statistical processing methods. The results that came from the data allow us to see the factors that have high impact upon the teachers ‘professional conduct and also the conditions of objectifying this professional conduct. The conclusions are significant for developing proper counselling programs addressed to parents that have child enrolled in kindergartens and to teachers that provided educational services for preschool children.